Kadar Glukosa Darah dan Laktosa Susu Pada Sapi Perah Dengan Pemberian Suplemen Herbal dan Mineral Proteinat - Nurul Yuliyani Imanto; Dian Wahyu Harjanti; Rudy Hartanto (Universitas Muhammadiyah Purworejo, 2018)
The aim of this research is to study the effect of herbal leaves papaya and turmeric, and Se and Zn proteinates on blood glucose, milk lactose, and can be used to improve milk production in dairy cattle. The material used is 16 livestock Friesian Holstein lactation, turmeric flour, papaya flour, mineral Se and Zn proteinates, and basal feed (elephant grass and concentrate). The design used was Completely Randomized Design with 4 treatments and 4 replications, T0 (basal feed), T1 (basal feed + herbal flour), T2 (basal feed + Se and Zn proteinates), T3 (basal feed + herbal flour + Se and Zn proteinates). Addition of herbal flour in the form 0.03% BW of turmeric and papaya leaves flour, Se and Zn proteinates given according to livestock shortage with dose Se 0,5 mg/kg BW and Zn 60 mg/kg BW. Parameters observed were blood glucose, milk lactose levels, and total milk production. The result showed that blood glucose level on T0, T1, T2 and T3 were 83,61; 82,33; 83,27 and 91,55 mg/dL. Milk lactose content in T0, T1, T2 and T3 were 4,38; 4,38; 4,48 and 4,42%. Milk production on T0, T1, T2 and T3 were 8,98; 11,58; 9,00 and 11,15 liters. There were no significant effects (P>0,05) of treatments in all parameters observed. Hence, it is concluded that the supplement herbal and mineral protein in lactating dairy cows did not alter blood glucose and milk lactose.